Нова Гребениківська стоянка на Південному Бузі - Сминтина, О.В.; Нікітін, В.І. (Археологія, 1996)
У статті розглядається історія вивчення мезоліту Побужжя i наводяться результати дослідження нової стоянки поблизу с. Пелагеївка Миколаївської обл. В статье рассматривается история изучения мезолита Побужья и приводятся результаты исследования нового местонахождения у с. Пелагеевка Новобугского района Николаевской обл. Присутствие в коллекции плоских нуклеусов гребениковского типа, трапеций, округлых скребков, небольшое количество резцов, типологически плохо выраженных, доминирование среди сколов правильных призматических пластинок и их сечений, практически полное отсутствие микроострий позволяет отнести стоянку к группе памятников гребениковской позднемезолитической культуры. По технологии расщепления кремня и характеру изделий со вторичной обработкой наиболее близкими аналогами Пелагеевке являются Гребеники, Гиржево, Доброжаны, Довжанка и другие на Нижнем Поднестровье.
Опираясь на выводы В.Н. Станко о путях сложения, зоне распространения и типичном индустриальном комплексе этой культуры, авторы связывают стоянку у с. Пелагеевка с расселением небольших охотничьих групп гребениковцев в поисках новых кормовых пространств по территории формирования и развития анетовской мезолитической культуры кукрекской культурно-исторической общности.
Феномен совместного обитания носителей этих двух культурных традиций при сохранении специфики своей материальной культуры и отсутствии выраженного взаимовлияния требует дальнейшего изучения. The history of the study of the mesolith in the Bug river territory and results of excavation of the new site near vil. Pelageyevka (the Novobug district, Nikolaev region) are described in this paper. Flat nuclei of the Grebeniki type present in the collection, as well as trapezia, round scrapers, some cutters, typologically poorly pronounced, predominance of regular prismatic plates and their sections among the spallings, practically absolute absence of micropoints have permitted attributing the site to the group of relics of Grebeniki late mesolithic culture. The procedure of flint splitting and pattern of articles with secondary treatment show that Pelageyevka has the most similar analogs in Grebeniki, Girzhevo, Dobrozhany, Dovzhanka and in some other sites in the lower Dniester territories.
Backing on the conclusions made by V. N. Stanko on the ways of formation, zone of propagation and typical industrial set of this culture, the authors link the site near vil. Pelageyevka with dispersion of small groupe of hunters from Grebeniki in search for new fodder spaces to the territory of formation and development of Anetovian mesolithic culture of the Kukrekian culture-historical community.
The phenomenon of combined residence of carriers of these two cultural traditions with retention of the specificity of the material culture and absence of the expressed mutual influence requires further study.